Multicultural-Based Islamic Religious Education: A Case Study at Al-Syifa Al-Khoiriyyah Islamic Boarding School, Subang - Rahardi, Gilang Tris; Wahid, Najihah Abd (BIRCU, 2025)
This study aims to explore the implementation of multicultural-based Islamic Religious Education at Al-Syifa Al-Khoiriyyah Islamic Boarding School in Subang. The background of this study is based on the urgency of strengthening the values of tolerance, diversity, and inclusivity in the Islamic education system amidst global social challenges. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation. The results of the study indicate that this Islamic boarding school strategically instills multicultural values through an integrated knowing (cognitive), feeling (affective), and action (practical) approach in the curriculum, learning activities, and daily lives of students. This educational model encourages the creation of a dialogic, tolerant learning community that is able to respond constructively to complex social dynamics. Theoretically, these findings contribute to the development of a more contextual and adaptive Islamic education framework to the reality of a multicultural society. While practically, this study offers a model of integration of multicultural values that can be used as a reference in developing curriculum and learning strategies in other Islamic educational institutions. However, this study has limitations in the scope of the location and the approach used, so the results cannot be generalized widely. Therefore, further studies with a mixed methods approach and a more diverse range of Islamic boarding schools are highly recommended. Multicultural-based Islamic education needs to continue to be developed as a contribution to humanist, inclusive, and equitable education on a local and global scale.